Edotia tangaroa sp. nov. (Crustacea: Isopoda: Idoteidae) from the western Ross Sea, Antarctica - Brandt, Angelika; Bruce, Niel (Zootaxa, 2006)
Edotia tangaroa sp. nov. is described from the western Ross Sea, Antarctica, the first record of the genus from that region. It is characterised by the dorsal ornamentation, consisting of numerous small, blunt tubercular, structures from the head to the tip of pleotelson, as well as short, blunt dorsal spines on basis of pereopods 1–7. Antenna 1 is slightly longer and more robust than antenna 2. An annotated species list is provided.